PEMBERDAYAAN PEREMPUAN MELALUI PARIWISATA EKONOMI KREATIF (KERUPUK GENJER) DI DESA ASINAN BAWEN KABUPATEN SEMARANG - Mistriani, Nina; Melda Hulu (ITB AAS Indonesia Surakarta, 2025)
This research aims to investigate the creative economy based on genjer crackers industry in Asinan Bawen Village, Semarang Regency, which has great potential to support local creative tourism. The traditional culinary industry enhances tourism appeal and increases community income. This research examines the dynamics of gender relations in the production, distribution, and promotion of genjer crackers as part of the creative tourism experience. This was conducted using an interpretive qualitative approach. Participatory observation, in-depth interviews, and document analysis were the methods used to obtain data. The results showed that women are responsible for the production and packaging processes, while men are responsible for product promotion and distribution. Economic and social aspects benefit women's participation, but are still limited by patriarchal social norms, limited access to capital, and lack of training.